2015
DOI: 10.1038/mp.2015.71
|View full text |Cite
|
Sign up to set email alerts
|

Association of percentile ranking with citation impact and productivity in a large cohort of de novo NIMH-funded R01 grants

Abstract: Previous reports from National Institutes of Health and National Science Foundation have suggested that peer review scores of funded grants bear no association with grant citation impact and productivity. This lack of association, if true, may be particularly concerning during times of increasing competition for increasingly limited funds. We analyzed the citation impact and productivity for 1755 de novo investigator-initiated R01 grants funded for at least 2 years by National Institute of Mental Health betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 13 publications
4
28
0
Order By: Relevance
“…A very detailed study shows that percentile scores cannot predict the productivity of almost 7,000 National Heart, Lung, and Blood Institute grants (35). In contrast to work Li and Agha (36, 37), Lauer et al (38) showed that study section scores are not discriminating predictors for proposals (39).…”
mentioning
confidence: 96%
“…A very detailed study shows that percentile scores cannot predict the productivity of almost 7,000 National Heart, Lung, and Blood Institute grants (35). In contrast to work Li and Agha (36, 37), Lauer et al (38) showed that study section scores are not discriminating predictors for proposals (39).…”
mentioning
confidence: 96%
“…Thus, it is unclear looking at an individual's career productivity alone may be an appropriate measure of success to validate review decisions; analysis of ex post productivity of individual projects is also required. (Berg, 2011;Fortin and Currie, 2013;Gallo et al, 2014) has predicted diminishing returns with larger investments; these studies found no correlation between review scores and output Doyle et al, 2015). However, a large NIH study of unnormalized bibliometric data found a moderate correlation (Li and Agha, 2015).…”
mentioning
confidence: 99%
“…Lindner and Nakamura 21 found that the bibliometric indexes of publications from funded projects are not an appropriate measure of the scientific impact of an application. Similarly, Kaltman et al 22 and Doyle et al 23 found no association between grant percentile ranking and an applicant's bibliometric indexes. Derrick et al 24 evaluated whether citation metrics correlated with peer assessment of a researcher's influence on his/her field.…”
Section: The Grant Itselfmentioning
confidence: 94%